Vaginal Fibroma Presenting as Paraurethral Mass Mimicking Cystocele: A case report - Bharati, Sonu (Europasian Journal of Medical Sciences, 2020)
Benign female paraurethral lesion encompasses a spectrum of entities that have significance in clinical urology. Fibromas are usually present in the uterus originating from the smooth muscles,however,vaginal fibroma is the extra uterine manifestation of leiomyoma. Here, we present a case of 45 years oldperimenopausalfemale, Para 6, living issues 6 who presented at our out-patientsdepartmentwith the complaint of mass growing in the vagina for 5 years but has increased in size for last 2 years. It has been associated with urinary symptoms, bleeding from mass and dyspareunia. General physical examinations were normal but on local examination mass arising from anterior vaginal wall mimicking cystocele with normal appearing external urethral meatus . However, her basic investigations including cystoscopy were normal. The tumor was surgically removed via myomectomy and its histopathology showed benign fibroma.